2016
DOI: 10.1016/j.ajp.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive remediation in schizophrenia—The view from India

Abstract: The prevalence and disability due to Schizophrenia (SZ) in India is similar to other parts of the world. Cognitive impairments are also present in a large group of Indian persons with SZ. Interventions to address these impairments – termed cognitive remediation or cognitive retraining – are being tested all over the world. Indian research on remediation in schizophrenia has been eclectic and is reviewed here. Some investigators have focused mainly on symptom control and quality of life, as yoga could be a cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Preliminary evidence treats the effectiveness of yoga as a complementary treatment in schizophrenia, but more research is needed to understand the mechanism by which yoga improves the symptoms of this disease. There are also reports of improved self-reflection in schizophrenic patients, highlighting that this intervention is economically and culturally acceptable, thus encouraging further research (Deshpande, et al, 2016).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Preliminary evidence treats the effectiveness of yoga as a complementary treatment in schizophrenia, but more research is needed to understand the mechanism by which yoga improves the symptoms of this disease. There are also reports of improved self-reflection in schizophrenic patients, highlighting that this intervention is economically and culturally acceptable, thus encouraging further research (Deshpande, et al, 2016).…”
Section: Discussionmentioning
confidence: 87%
“…Patients with schizophrenia treated with antipsychotics underwent treatment with yoga in order to reduce the signs and symptoms of the disease (Cherubal, et al, 2019;rao & menon, 2016), such as the depression and cognitive correction in schizophrenia (Bhatia, et al, 2017;Cherubal, et al, 2019;Deshpande, et al, 2016). This intervention resulted in an improvement in general attentional skills (Deshpande, et al, 2016), and reduced depression and anxiety stress, generating well-being (Cherubal, et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially used for brain-damaged patients, CR use was extended to schizophrenia ( 13 ), and later to several pediatric mental health conditions. CR effectiveness was demonstrated in children and adolescents with attention deficit hyperactivity disorder (ADHD) ( 14 ), anorexia nervosa ( 15 , 16 ), specific learning disorder ( 17 ), intellectual disability ( 18 ) and in early onset psychosis ( 19 ).…”
Section: Effects Of Cr In Children and Adolescents With Asdmentioning
confidence: 99%
“…Research has shown benefits in mental disorders, such as depression, anxiety, and psychosis (Varambally & Gangadhar, 2016). Increasingly, Yoga is seen as an indigenous model of rehabilitation throughout parts of Asia, assisting with symptom control and quality of life, which could be a cost-effective and culturally acceptable intervention (Deshpande, Bhatia, Mohandas, & Nimgaonkar, 2016). Varambally and Gangadhar (2016) argue that yoga can be an adjunct to standard treatment and potentially a treatment on its own.…”
Section: Translating Evidence Into Practice Examples Of Adaptation Omentioning
confidence: 99%